Guest

24th question in the attachment.......... ......................................

24th question in the attachment..........  ......................................

Question Image
Grade:12

1 Answers

Vikas TU
14149 Points
2 years ago
Dear student 
f(y) = e^y 
f(t-y) = e^(t-y)
F(t) =  ∫e^t e^-y *y dy 
Use ILATE Rule 
and apply limit between 0 to t 
F(t) = e^t -(1+t) 
Goo Luck 

Think You Can Provide A Better Answer ?

Provide a better Answer & Earn Cool Goodies See our forum point policy

ASK QUESTION

Get your questions answered by the expert for free